Presidents and civil liberties from Wilson to Obama : a story of poor custodians / Samuel Walker. - Walker, Samuel, 1942- (Cambridge University Press, 2012)
This book is a history of the civil liberties records of American presidents from Woodrow Wilson to Barack Obama. It examines the full range of civil liberties issues: First Amendment rights of freedom of speech, press and assembly; due process; equal protection, including racial justice, women's rights, and lesbian and gay rights; privacy rights, including reproductive freedom; and national security issues. The book argues that presidents have not protected or advanced civil liberties, and that several have perpetrated some of the worst violations. Some Democratic presidents (Wilson and Roosevelt), moreover, have violated civil liberties as badly as some Republican presidents (Nixon and Bush). This is the first book to examine the full civil liberties records of each president (thus, placing a president's record on civil rights with his record on national security issues), and also to compare the performance on particular issues of all the presidents covered.